(untitled) (Canadian Journal of Counselling and Psychotherapy, 2018)
Embodiment is a long-standing concept which has resurfaced in the last few decades as an important construct for many disciplines. Understanding embodiment is imperative in a therapeutic setting because it impacts both mental and physical health through intrapersonal and interpersonal experiences. This research explored how 10 women described their experiences of positive embodiment in a Western sociocultural context. Qualitative interview data was analyzed using constructivist grounded theory. Preliminary results from this research suggest that women engage in continuous meaning making and balancing in order to maintain positive embodiment. Implications for counselling and future research in psychology are discussed.